Rozwiązania logistyczne w przedsiębiorstwach przetwórstwa mleka jako jedno ze źródeł przewagi konkurencyjnej - Drelichowski, Ludosław; Sikora, Marek (The Logistic Solutions of Milk Processing Enterprises as One of the Sources of Competitive Advantage, 2006)
The analysis of logistic solutions of chosen milk processing enterprises as a source of competitive advantage allows to affirm that the wide scale of workings in the logistics of purchase is favourable to the improvement of quality of material and to the lowering of the costs of transportation. The half from the studied objects can't undertake a decision about organizational integration with leaders of the creamery sector choosing this as a chance of enlargement of competitive advantage.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1118, t. 1, s. 187-193